Педагогическое взаимодействие в образовательном процессе высшей профессиональной школы - Nabiev V. S. (Pedagogical excellence and pedagogical technologies, 2017)
the author proposes a subject-subject educational interaction process participants to consider how the success of the formation of competence approach in higher professional school
Keywords: компетентностный подход; образовательный процесс; educational process; Competence approach